Biocompatible and Biodegradable Neuromorphic Device Based on Hyaluronic Acid for Implantable Bioelectronics. (12th September 2021) - Lee, Jin Hyeok; Rim, You Seung; Min, Won Kyung; Park, Kyungho; Kim, Hyung Tae; Hwang, Gyuho; Song, Jaewhan; Kim, Hyun Jae
Abstract: Neurodegenerative disorders are challenging issues for initial diagnosis and cure. False signals from neurons that make up the brain must be corrected. To treat neurodegenerative diseases, neuromorphic devices are inserted into the body and connected to nerves. However, there are major concerns regarding implanting these devices into living bodies, that is, toxicity caused by the materials and the need for an additional operation to remove the device after treatment. In this research, a neuromorphic device is fabricated based on hyaluronic acid (HA), which is biocompatible and biodegradable, that meets the requirements for implantable bioelectronics. The fabricated device have a paired‐pulse facilitation index of ≈121.00% and short term‐to‐long term memory transition behavior that resembled human learning‐experience behavior. It is confirmed that the synaptic behavior mechanism of the device is due to an Mg oxide layer formed at the Mg/HA interface. Biodegradability and cell cytotoxicity tests confirmed the suitability of HA‐based neuromorphic devices as implantable bioelectronics. Based on the results, it is believed that such implantable devices will lead to better healthcare. Abstract : Conventionally, hyaluronic acid (HA) is a biosynthetic natural material that is present in the skin and is biocompatible and biodegradable. Here, the use of HA as the switching layer of the neuromorphic device is reported for the first time, a material that meets the requirements for implantable bioelectronics.